Theta burst stimulation on the fronto-cerebellar connective network promotes cognitive processing speed in the simple cognitive task - Zhao, Ning; Tao, Jing; Wong, Clive; Wu, Jing-song; Liu, Jiao; Chen, Li-dian; Lee, Tatia M. C.; Xu, Yanwen; Chan, Chetwyn C. H. (Frontiers in Human Neuroscience, 2024)
Background: The fronto-cerebellar functional network has been proposed to subserve cognitive processing speed. This study is aimed to elucidate how the long-range frontal-to-cerebellar effective connectivity contributes to promoting faster speed. Methods: Sixty healthy participants were randomly allocated to three five-daily sessions of transcranial magnetic stimulation conditions, namely intermittent theta-burst stimulation (iTBS, excitatory), continuous theta-burst stimulation (CTBS, inhibitory), or a sham condition. The sites of the stimulations were the RpSMA, MCV6 and Vertex, respectively. Performances in two reaction time tasks were recorded at different time points. Results: Post-stimulation speeds revealed marginal decreases in the simple but not complex task. Nevertheless, participants in the excitatory RpSMA and inhibitory MCV6 conditions showed direct and negative path effects on faster speeds compared to the sham condition in the SRT task (β= - 0.320, p=0.045 and β= - 0.414, p=0.007, respectively). Such path effects were not observed in the SDMT task. Discussion: RpSMA and MCV6 were involved in promoting path effects of faster reaction times on simple cognitive task. This study offers further evidence to support their roles within the long-range frontal-to-cerebellar connectivity subserving cognitive processing speed. The enhancement effects, however, are likely limited to simple rather than complex mental operations.